Response due to mechanical source in second axisymmetric problem of micropolar elastic medium - Singh, R. (Zielona Góra: Uniwersytet Zielonogórski)
The second axisymmetric problem in a micropolar elastic medium has been investigated by employing an eigen value approach after applying the Laplace and the Hankel transforms. An example of infinite space with concentrated force at the origin has been presented to illustrate the application of the approach. The integral transforms have been inversed by using a numerical technique to obtain the components of microrotation, displacement, force stress and couple stress in the physical domain. The results for these quantities are given and illustratred graphically.
Keywords: eigen value; micropolar elastic medium; Laplace transforms; Hankel transform; concentrated force; microrotation; Rhomberg`s integration